Sustainable Approach to Superhydrophobic Surfaces Based on Water‐Born Electrospinning. Issue 9 (10th July 2018) - Doimoto, Mitsunobu; Greiner, Andreas
Abstract: Superhydrophobic surfaces are obtained by a sustainable approach by electrospinning of water‐based acrylate dispersion followed by mild silanization and removal of template polymer. The resulting nonwovens show very high superhydrophobicity and very low roll angle. In contrast to many other approaches, pores provide the required morphology to achieve superhydrophobicity. This new material provides a new approach to electrospun nonwoven coatings which can be of interest for textile applications. Abstract : A green water‐based approach to the formation of superhydrophobic and self‐cleaning polymeric surfaces is demonstrated. The hierarchical porous fibrous surface created by differential wetting to the contact angle >160° and roll angle 0°, that is, water rolls at a horizontal surface and thereby provides a novel approach to self‐cleaning surfaces.